2000
DOI: 10.1177/0022427800037001003
|View full text |Cite
|
Sign up to set email alerts
|

Relative Deprivation and Deviant Adaptations: The Mediating Effects of Negative Self-Feelings

Abstract: Theoretically informed models are estimated that specify individual-level effects of relative deprivation (using diverse comparison groups), mediated by negative self-feelings, on different modes of deviant adaptations. The models are estimated by using multivariate logistic regression techniques on survey data (N = 6,074). In general, the results are consistent with the hypothesis that perceived economic deprivation relative to friends, neighbors, and the nation induces negative self-feelings, which, in turn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…Stiles, Liu, and Kaplan (2000) analyzed a single wave of panel data collected from more than 6,000 subjects, who were surveyed when they were in their mid-to-late twenties. They found that the fit of several multivariate models that considered self-assessments of deprivation (relative to friends, neighbors, and perceived national averages) improved when negative self-feelings were included as an independent variable.…”
Section: The School-strain Relationshipmentioning
confidence: 99%
“…Stiles, Liu, and Kaplan (2000) analyzed a single wave of panel data collected from more than 6,000 subjects, who were surveyed when they were in their mid-to-late twenties. They found that the fit of several multivariate models that considered self-assessments of deprivation (relative to friends, neighbors, and perceived national averages) improved when negative self-feelings were included as an independent variable.…”
Section: The School-strain Relationshipmentioning
confidence: 99%
“…When this occurs, the individual may feel as if he or she has been unjustly deprived of some desired thing, resulting in feelings of anger, resentment, grievance, moral outrage, envy, or low self-worth. According to the research conducted by Kaplan and his colleagues (Kaplan, 1980;Stiles et al, 2000) relative deprivation may also lead to negative self-feelings. These negative self-feelings, in turn, result in socially unacceptable behaviors (i.e., unethical behavior) as a way for the individual to restore self-esteem.…”
mentioning
confidence: 99%
“…Public health studies have found negative effects on stress, depression, heart disease, high blood pressure, suicide, eating habits, alcohol abuse, and mortality~Eibner, 2000; Deaton, 2001;Long, Lynch, Machiran, Thomas, & Malinow, 1982!. Sociological research has linked relative deprivation with social protest, violent crime, property crime, and drug use~Canache, 1996; Schulz, 1998;Stiles, Liu, & Kaplan, 2000!. In fact, the term "relative deprivation" is often used to refer to the negative feelings that arise from having less than others.…”
mentioning
confidence: 99%